Surface modified EuxLa1-xF3 nanoparticles as luminescent biomarkers: Still plenty of room at the bottom. (August 2017) - Khudoleeva, Vladislava Yu.; Utochnikova, Valentina V.; Kalyakina, Alena S.; Deygen, Irina M.; Shiryaev, Andrey A.; Marciniak, Łukasz; Lebedev, Vasiliy A.; Roslyakov, Ilya V.; Garshev, Alexey V.; Lepnev, Leonid S.; Schepers, Ute; Bräse, Stefan; et al.
Abstract: Investigation of the formation and luminescent properties of surface modified bimetallic lanthanide fluorides and their use in bioimaging is described. We have shown that the solvent during the wet synthesis of EuF3 nanoparticles affects the nanoparticle morphology, which in turn influences the conditions of its phase transition from hexagonal to orthorhombic. The morphology of bimetallic Eux La1-x F3 depends on the europium fraction x, allowing nanoparticles of ca. 50 nm to be obtained. Surface modification with aromatic carboxylates (L) allowed luminescence intensity increase by two orders magnitude, while luminescence quantum yield (PLQY) dependence on Eu fraction was shown to be affected by the ligand L: so, when L = 2, 6-naphtalenedicarboxylate, PLQY reached its maximum of 70% at x = 0.3, while when L = terephthalate, almost no quantum yield decrease was observed for 0.01 < x < 0.3 (PLQY = 70 ± 5%). Nanoparticles solubilized in water were obtained by different polymer immobilization of the particle surface, and the use of poly(vinylpyrrolidone) (PVP) resulted in the formation of non-toxic nanoparticles PVP@L@Eu0.3 La0.7 F3, which uniformly distributed in cell cytoplasm and exhibited intensive luminescence in cells. Highlights: Surface modified bimetallic fluorides were proved to emit with the whole particle volume and not only the surface Eu atoms. Quantum yield of tph@Eux La1−x F3 (tph = terephthalate) remained almost constant at x = 0.3…0.01 due to multiphotonic emission. The first example of the morphology-dependent phase transition was demonstrated for EuF3 nanoparticles. Luminescence and size optimization allowed obtaining soluble and biocompatible nanoparticles brightly emitting in cellulo .